Effect of hydrothermal pretreatment on pyrolyzed sludge biochars for tetracycline adsorption. Issue 6 (December 2021) - Chen, Weisheng; Zhao, Baolong; Guo, Yiping; Guo, Yujie; Zheng, Zhihong; Pak, Tannaz; Li, Guoting
Abstract: In this research, two biochars derived from activated sludge (wastewater treatment plant) are prepared by two different preparation processes for the comparative studies of tetracycline (TC) adsorption. One is the two-stage process, including hydrothermal pretreatment and subsequent high-temperature pyrolysis (HSBC-600), while the other is the direct pyrolysis method (PSBC-600). Various technologies are employed to characterize physicochemical properties and structural features of the two biochars. The results indicate that hydrothermal pretreatment can increase the specific surface area (133.4 and 114.6 m 2 /g for HSBC-600 and PSBC-600) and pore volume (0.237 and 0.159 cm 3 /g for HSBC-600 and PSBC-600) of biochar. At 298 K, the q max on HSBC-600 and PSBC-600 achieves 116.9 and 89.3 mg/g, respectively. It is noted that the Freundlich isotherm and pseudo-second-order kinetic equations better describe the adsorption behavior, indicating that the adsorption of TC onto HSBC-600 and PSBC-600 is the multi-layer adsorption and involves chemical adsorption. The thermodynamic parameters reveal that the adsorption process is spontaneous and endothermic, causing an increase in the degree of disorder. All adsorption mechanisms may be consisted of pore filling, electrostatic force, hydrogen bond, and π-π interaction. The higher adsorption capacity of HSBC-600 could be attributed to the more adsorption sites provided from high specific surface area and pore volume, in which π-π interaction plays a major role. Graphical Abstract: ga1 Highlights: Two different approaches are applied to prepare sludge-based biochars for the adsorption of TC. Biochar prepared by hydrothermal pretreatment exhibits better adsorption performance. The Freundlich isotherm and pseudo-second-order kinetic models better describe the experimental data. All adsorption mechanisms contain pore filling, electrostatic force, hydrogen bond, and π-π interaction.